FINANCING MANAGEMENT OF PUBLIC MADRASATSANAWIYA IN CENTRAL BENGKULU DISTRICT (The Journal of Educational Development, 2015)
Madrasa is now much demanded by the public. However, getting a quality education in madrasa requires high cost and quality management. By using a qualitative approach, this study aims to analyze the financing management in Public Madrasa Tsanawiyah (MTs) in Central Bengkulu district that focuses on: (1) planning, (2) implementation, and (3) monitoring. The results showed that public MTs in Central Bengkulu district: (1) the Financing planning in madrassas is routinely carried out prior to the following year budget implementation with the following stages: the principals of the madrassa learn the vision, mission, programs and activities in the future, then the principals invite teachers and committee to draft RAPBM. After that, RAPBM is sent to the Regional Office for the preparation of RKKS planning and DIPA proposals in the upcoming year; (2) The financing implementation in school is done after each disbursement, expenditure, accounting, until reporting in each month; (3) The financing control in madrassas is conducted in madrassas. And the agencies that participate in the supervision and internal audit madrasah are Iten, BPKP and the Ministry of Religious Affairs (MORA) of provinces/districts level.